The Role of Microbial Activity in Suppression of Damping-Off Caused by Pythium ultimum - Chen, Weidong; Hoitink, A J; Schmitthenner, A Fritz; Tuovinen, Olli H (Phytopathology, 2025)
Addition of nutrients increased Pythium damping-off severity in a suppressive container medium amended with bark compost from the low temperature edge of a compost pile. A significant linear response of disease severity to added nutrients was observed. Levels of seed exudation were directly related to damping-off severity for seeds of a cucumber, a smooth-seeded, and a wrinkled-seeded pea cultivar. Container media amended with compost from the high temperature center of a compost pile (> 60 C) were conducive to the disease at first but became suppressive in 3 to 4 days after incubation at 25 C, as they became recolonized by mesophilic microorganisms. Initially concentrations of water extractible glucose, reducing sugars, and total carbohydrates in the center compost medium were higher than those in the edge compost medium. However, concentrations decreased to levels not significantly different from those in the edge compost medium after 1, 4, and 6 days, respectively. These reductions in carbohydrate concentrations coincided with an increase in suppression in the medium prepared with high temperature compost. This increase with time was highly correlated with microbial activity, based on rates of hydrolysis of fluorescein diacetate ( = -0.919, < 0.001), and also correlated with total biomass, based on extractible phospholipid phosphate ( = -0.509, < 0.003). Populations of mesophilic bacteria, actinomycetes, and total fungi in the conducive high temperature compost-amended medium were significantly lower in the first 2 days after incubation at low temperature. After 4 days, populations had increased to levels similar to those in the medium amended with low temperature compost, and they stayed at that level thereafter. Percent infection of cucumber and germination of sporangia were significantly higher in the conducive than in the suppressive container medium. Infection of cucumber occurred before populations increased significantly. It was concluded that coexistence of large populations of mesophilic microorganisms, great microbial activity, low concentrations of available nutrients, and high degree of microbiostasis characterized container media suppressive to Pythium damping-off.